IFPRI and AgMIP Results from Recent Assessments - De Pinto, Alessandro (2017)
IFPRI Senior Research Fellow Alessandro De Pinto gave this presentation at the annual forum of the Global Alliance for Climate Smart Agriculture (GACSA) held at FAO Headquarters in Rome in December 2017 (https://www.fao.org/gacsa/annual-forum/en/).